Analisis Produktivitas Tenaga Kerja Perhitungan Lapangan Pada Konstruksi Bangunan Gedung Pada Pembangunan Gedung Mall Pelayanan Publik Kabupaten Gowa – Sulawesi Selatan - Zakyahutami, Fadma Rany; Abduh, Muh. Natsir; Mulyani, Savitri Prasandi (Jurnal Penelitian Teknik Sipil Konsolidasi, 2025)
Productivity is a major factor that greatly influences the competition in building construction, where the level of productivity is related to the time needed complete his work which will directly affect the amount of costs required. Therefore, information on labor productivity is very important to be studied in detail. One way to obtain field productivity values  to use the work sampling method. In this study, observations were made for 12 weeks for basement work (Ground Floor). Based on the research that has been conducted, the results of the analysis show that work productivity in the field is higher than based on the SNI 2023 plan, namely in bored pile work by 0.30 times, in plain iron work by 0.10 times, in threaded iron work by 0.07 times, in the installation of foundation formwork by 0.26 times, in the installation of sloof formwork by 0.35 times, in the installation of column formwork by 0.14 times, in the installation of beam formwork by 0.15 times, in concrete work f'c 7.4 mpa K100 by 0.84 times, in concrete work f'c 26.4 mpa K300 by 0.47 times, in practical reinforcement column work by 0.23 times, and in crushed stone foundation work by 0.12 times.